ВИКОРИСТОВУВАННЯ САМОСТІЙНОЇ РОБОТИ НА ЗАНЯТТЯХ З АНГЛІЙСЬКОЇ МОВИ, ЯК ЗАСІБ ПІДВИЩЕННЯ ЯКОСТІ ЗНАНЬ МАЙБУТНІХ ФАХІВЦІВ (Педагогіка вищої та середньої школи, 2008)
In article problems of use of independent work of students on employment on English language in the higher school, as way of improvement of quality of knowledge are considered.